The use of flowable bulk-fill resin composite entire cavity is a less time-consuming approach for occluso-proximal restorations in primary teeth - Clara Cavagnoli Mendes; Cleber Paradzinski Cavalheiro; Carolina Lopes da Silva; José Carlos Pettorossi Imparato; Tathiane Larissa Lenzi (Revista da Faculdade de Odontologia de Porto Alegre)
Aim: To compare the time required to perform occluso-proximal restorations using different flowable resin composites (as an intermediate layer or entire cavity) with conventional resin composite (incremental technique). Materials and methods: Two standardized cavities were prepared on occluso-mesial and occluso-distal surfaces of fifty sound primary molars. After application of a universal adhesive system (Scotchbond Universal) in the self-etch mode, the teeth were randomly assigned into five groups (n=10): G1: 2mm of Filtek Bulk Fill Flow + Filtek Z350 XT;  G2: 4mm (single increment) of Filtek Bulk Fill Flow; G3: 2mm of Filtek Z350 XT Flow + Filtek Z350 XT; G4: 4mm (two increments) of Filtek Z350 XT Flow, and G5: Filtek Z350 XT. The time required to perform the restorations since the insertion of the first increment of resin composite in the first cavity (occluso-mesial) until the light-curing the last increment in the later cavity (occluso-distal) was measured in minutes using a digital chronometer. Data were submited to one-way ANOVA and Tukey’s post-hoc tests. Results: The ranking of higher to less time was G5 > G1 = G3 > G4 > G2 (p=0.00). Discussion: The use of flowable resin composites to fill the whole cavity is attractive in clinical practice, considering the limited functional time of primary teeth and the varying cooperation of the child patient. Conclusion: Single use of flowable bulk-fill resin composite and the use of conventional resin composite are the less and more time-consuming approaches for occluso-proximal restorations in primary teeth, respectively.